Breastfeeding Failure and Determinants: A Qualitative Study in Indonesia - Fadjriah, Rasyika Nurul; Krishnasari, Shendy (Diversity: Disease Preventive of Research Integrity, 2022)
Exclusive breastfeeding has a significant impact on the growth and development of children. The low coverage of exclusive breastfeeding has significantly contributed to stunting in this country. This study aimed to describe the determinants of the failure of exclusive breastfeeding from the aspect of the mother's knowledge, breast problems, family support, support from health workers, and traditions. The research method was qualitative with a case study design. The sampling technique used purposive sampling with 34 mothers and five cadres. Data was collected using FGD (Focus Group Discussion) and In-depth Interviews. Data analysis using content analysis and data validation using triangulation techniques. The results showed that the dominant mother did not know about exclusive breastfeeding. Breast problems were the dominant determinant of the failure of exclusive breastfeeding. Families and health workers had not provided good social support to mothers. The tradition found was providing sugar water and rice water to infants aged less than 6 (six). This study found that maternal knowledge, breast problems, family support, support from health workers, and traditions were the determinants of the failure of exclusive breastfeeding. This study recommends the need for education for mothers, families, and health workers to understand the urgency of exclusive breastfeeding.